Antimicrobial residues in bovine muscle tissue and kidneys expended in Piura supermarkets, Peru - Guerra Delgado, Marco Sergio (2021)
The objective of the study was to determine the presence of antimicrobial residues in bovine muscle tissue and kidneys expended in supermarkets of the Piura city, Peru. 100 muscle tissue samples were collected from the loin and tip of the hip, free of fat and aponeurosis, and 100 samples from kidneys. From each sample obtained, 8 mm diameter and 2 mm thick pieces were analyzed and deposited on a culture medium mixed with Bacillus subtilis spores adjusted to pH 6.0; 7.2 and 8.0. Based on the size of the growth inhibition halo of the strain, it was found that 23 samples were positive for the detection of antimicrobial residues. 5% (5/100) corresponded to muscle tissue samples and 18% (18/100) to kidneys. The highest number of positive samples was obtained in supermarkets I (2 for muscle tissue and 7 for kidney) and II (2 for muscle tissue and 6 for kidney). The mean and standard deviation of the inhibition halo in the positive samples were, respectively, 4.4 and 0.7 for the muscle tissue samples and 5.0 and 1.3 in the case of kidney samples. The study concludes that there is the presence of antimicrobial residues in muscle tissue and kidney of cattle expended in Piura city supermarkets, diagnosed with the Bacillus subtilis technique, which is a quick and simple method used to detect these residues in the products of the bovines commercialized.